Konsep Makanan Halal: Mie Gomak Medan Sebagai Kuliner Khas Sumatera Utara - Syariah Hafizhoh; Della Latifah Amanda; Sriwahyuni Sriwahyuni; Rini Antika Sari; Nanda Ayuningtyas; Khoridatunnida Khoridatunnida; Alwi Umar; Aldi Maulana; Arjuna Barkah Firdaus (Universitas Katolik Widya Karya Malang, 2023)
This journal examines the halalness of one of Medan's culinary specialties, namely Mie Gonak. Mie Gomak is a type of typical Medan culinary food which is famous for its delicacy. Included in the type of processed food in the form of typical Medan noodles combined with processed Italian noodles. These foodstuffs are relatively cheap, so they are in great demand by the lower middle class, especially the young. From there, the idea emerged to make a business breakthrough in the form of culinary food, namely Mie Gomak, whose target market is almost all people. This culinary specialty of Mie Gomak Medan will be packaged simply in an attractive package, does not require too much space, and is easy to manufacture and sell. Buyers only buy, then can take it to another place to consume it. This business is easy, simple and does not really require large capital, so anyone can do it. And this culinary includes food that is halal for consumption, because in terms of the ingredients, everything is halal.